In search of new paradigms for epididymal health and disease: innate immunity, inflammatory mediators, and steroid hormones - Avellar, M. C. W.; Ribeiro, C. M.; Dias-da-Silva, M. R.; Silva, E. J. R. [UNESP] (Wiley-Blackwell, 2019)
The primary job of the epididymis is to mature and protect the luminally transiting spermatozoa. Mounting evidence is showing that innate immune components [including Toll-like receptors (TLRs) and antimicrobial proteins, among which are beta-defensins] and inflammatory mediators, under the primary influence of androgens, participate in the cellular and molecular processes that define this tissue. Here, we present an overview of the contributions of these signaling pathway components during epididymal homeostasis and discuss the hypotheses as to their involvement in epididymitis, the most common urological inflammatory condition in men, frequently impairing their fertility. Drawing primarily from rodent models, we also focus on how the distribution and functional expression of innate immune components are differentially regulated in the prenatal developing epididymis, providing new insights into the disruption of these signaling pathways throughout the lifespan. Male infertility is caused by a variety of conditions, such as congenital malformations, genetic and endocrine disorders, exposure to environmental toxicants, and inflammatory/infectious conditions. More than one-third of infertile men with an idiopathic condition cannot currently be adequately diagnosed. Thinking about the innate immunity and inflammation context of the epididymis may provide new insights and directions as to how these systems contribute to male fertility, as well as also uncover urological and andrological outcomes that may aid clinicians in diagnosing and preventing epididymal pathologies.
Keywords: androgens; developmental origins of health and disease; epididymis; infertility; inflammatory disorders; innate immunity